2021
DOI: 10.1038/s41598-021-97487-x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ cafeteria diet induced sex-specific changes in fat content, metabolic profiles, and inflammation outcomes in rat offspring

Abstract: Abstract“Western diet” containing high concentrations of sugar and fat consumed during pregnancy contributes to development of obesity and diabetes type 2 in offspring. To mimic effects of this diet in animals, a cafeteria (CAF) diet is used. We hypothesized that CAF diet given to rats before, and during pregnancy and lactation differently influences fat content, metabolic and inflammation profiles in offspring. Females were exposed to CAF or control diets before pregnancy, during pregnancy and lactation. At p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(99 reference statements)
2
14
1
Order By: Relevance
“…Similarly, Samuelsson et al have found that in the offspring of HFHSD mothers, adult male mice were heavier than females (12). Matuszewska et al (18) observed that on postnatal day (PND) 25 both male and female offspring of the dams fed a CAF diet had lower body weights than the animals in the control group. However, there was no difference in this parameter on PND 3.…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 90%
See 3 more Smart Citations
“…Similarly, Samuelsson et al have found that in the offspring of HFHSD mothers, adult male mice were heavier than females (12). Matuszewska et al (18) observed that on postnatal day (PND) 25 both male and female offspring of the dams fed a CAF diet had lower body weights than the animals in the control group. However, there was no difference in this parameter on PND 3.…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 90%
“…Moreover, among the four-week offspring of CAF mothers the males had a higher perirenal fat mass than the females, whereas the females had a greater gonadal fat content than the males (28). Matuszewska et al (18) observed that both the male and female offspring of mothers receiving a CAF diet for four weeks before pregnancy, and then during pregnancy and lactation, had a lower fat content on PND 25, but these changes were more pronounced in the female CAF offspring.…”
Section: Effects Of Maternal Overnutrition On Body Weight and Fat Con...mentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies involving maternal consumption of obesogenic diets use the HFD model. However, the cafeteria diet (CAF) model provides animals with ultra-processed human food consumption and has translational potential (Matuszewska et al, 2021). Wright et al showed that maternal consumption of a CAF impacts offspring behaviour, regardless of whether consumption occurs in the preconception period, during pregnancy, lactation, or all these periods (Wright et al, 2011).…”
Section: Anxietymentioning
confidence: 99%